Aprender linguagem de programação no ensino fundamental com a ferramenta Scratch: sentidos construídos por estudantes - Bisneta, Maria Luiza Soares da Silva (Universidade Federal Rural do Semi-Árido, 2019)
Computing is driving job creation and innovation throughout our economy and society. “Today, to be well-educated citizens in an Information Technology-permeated world, everyone must have a clear understanding of computing principles and practices beyond the simple use of IT” von Wangenheim, Nunes & Santos (2014, p. 116). This paper aims to analyze meanings built by students of the early years of elementary school about their learning in programming language using the Scratch tool in the educational process. To this end, the “Scratch: Bring Your Imagination” extension project, developed by students from the Computer courses at the UFERSA Campus in Angicos / RN, had as its perspective the objective of providing for elementary students in the 4th grade. and 5th year of CEPA - Doctor Pedro Amorim Educational Center, the teaching of basic computing concepts related to the teaching of programming logic, for students who have never had contact with the teaching of programming. Teaching programming logic transfers a more organized thinking to the child, boosts creativity and is the first step to learning a programming language, offers the child new learning possibilities, because the school must teach everything that is real, current. within the context of the students and this includes the teaching of computer science. The methodological proposal of the field research was used questionnaires, to obtain the quantitative and qualitative results. With the tabulation of the questionnaires, the graphs show that the teaching of computer science, within the programming of computers with elementary school students by their perception and meanings, should be integrated into the school curriculum, because besides the affection and interest they had with the content and the tool show that they find it important to be studied. Given that these technologies are part of students 'daily life, within the context in which they are inserted, the school would have an improvement in student performance in other subjects, according to the students' perspectives. The constructed senses of these students is a sample that in the northeastern urban context of the interior children already show interest in studying the logic of programming. It is believed that depriving students of knowledge on subjects of interest is taking opportunities from future professionals in this field.
Monografia
Keywords: Sentidos das crianças; Lógica de programação; Scratch; Children's senses; Programming logic; Scratch; CIENCIAS EXATAS E DA TERRA::COMPUTACAO E INFORMATICA